2009
DOI: 10.1071/cp08170
|View full text |Cite
|
Sign up to set email alerts
|

The first century of Phalaris aquatica L. cultivation and genetic improvement: a review

Abstract: 2006 marked the centenary of the commercial propagation of phalaris (Phalaris aquatica L.) as a cultivated pasture plant, firstly in Australia, and soon after in New Zealand, South Africa, and North and South America. Small-scale evaluation of cv. Australian began in the Toowoomba Botanic Gardens, Queensland, in 1884. The first recorded large-scale production of seed was at the Glen Innes Research Farm of the NSW Department of Agriculture in February 1906. By 1908–15, several graziers in Australia and New Zeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 61 publications
0
41
0
Order By: Relevance
“…This argument can be extended to include the other temperate perennial grass species, phalaris and perennial veldt grass, even though this study did not include contrasting cultivars of these species. The phalaris cultivar included in the current study, Landmaster, was chosen for its adaptability to acid soil environments and could be considered to be moderately summer-active (Oram et al 2009). This cultivar, which is perhaps not the most persistent phalaris cultivar under drought, still proved to have equal or greater persistence than any other grass species evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…This argument can be extended to include the other temperate perennial grass species, phalaris and perennial veldt grass, even though this study did not include contrasting cultivars of these species. The phalaris cultivar included in the current study, Landmaster, was chosen for its adaptability to acid soil environments and could be considered to be moderately summer-active (Oram et al 2009). This cultivar, which is perhaps not the most persistent phalaris cultivar under drought, still proved to have equal or greater persistence than any other grass species evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Oram et al. () reported that phalaris had excellent persistence in areas with >600 mm average rainfall. Oram and Hoen () found that North African germplasm with higher levels of summer dormancy, but which were also earlier flowering and more winter‐active survived better in cropping areas with 450–500 mm rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, attempts have been made to introduce and incorporate genes from plants of low rainfall origin, such as the Mediterranean and North Africa. Australia was one of the first countries to deliberately exploit Mediterranean ecotypes of perennial grasses, due to climatic similarities, the value of pasture plants from the regions and the discovery and domestication of the Mediterranean grass phalaris (Culvenor, 2009;Oram et al, 2009). The adaptation of the perennial temperate grasses into lower rainfall environments has been substantially expanded in Australia by the replacement of early northern European introductions with more drought-hardy and summer-dormant germplasm from Mediterranean regions (Culvenor, 2009).…”
Section: Development Of New Perennial Grassesmentioning
confidence: 99%